Vapor-liquid equilibria for difluoromethane plus dichloromethane at 305.2 and 313.2 K and 1,1-difluoroethane plus vinyl chloride at 303.2 and 323.2 K - Lim, JS; Lee, YW; Lee, YY (AMER CHEMICAL SOC, 1997)
Isothermal vapor-liquid equilibria for difluoromethane (HFC-32) + dichloromethane at 303.2 K and 313.2 K and 1,1-difluoroethane (HFC-152a) + vinyl chloride at 303.2 K and 323.2 K were measured in a circulation-type apparatus. The experimental data were correlated with the Peng-Robinson equation of state using the Wong and Sandler mixing rule, and the relevant parameters are presented.
Keywords: MIXING RULE; STATE; EQUATION